Synthesis of a 3-Amino-2,3-dihydropyrid-4-one and Related Heterocyclic Analogs as Mechanism-Based Inhibitors of BioA, a Pyridoxal-Phosphate (PLP) Dependent Enzyme - Eiden, Carter G. (J Org Chem, 2017)
Amiclenomycin (ACM) is a chemically unstable antibiotic with selective activity against Mycobacterium tuberculosis (Mtb) due to mechanism-based inhibition of BioA, a pyridoxal 5′-phosphate (PLP) dependent aminotransferase. The first-generation ACM analogue dihydro-2-pyridone 1 is semi-stable and maintains a similar bioactivation mechanism concluding with covalent labeling of the PLP cofactor. To improve on 1, we report the synthesis of dihydro-4-pyranone 2, dihydro-4-pyridone 3 and dihydro-4-thiopyranone 13, which were rationally designed to boost the rate of enzyme inactivation by lowering the pK(a) of their α-protons. We employed a unified synthetic strategy for construction of the desired heterocycles featuring α-amino ynone generation followed by 6-endo-dig cyclization. However, competitive 5-exo-dig cyclization, β-elimination of the ynone, and dimerization of the resultant α-amino carbonyls all complicated the syntheses of the dihydro-4-pyranone and dihydro-4-pyridone scaffolds. These obstacles were overcome by Teoc protection of the β-amino group in the assembly of 3 and Boc-MOM protection of the α-amino group in the synthesis of 2, enabling the efficient construction of 2 and 3 in seven steps from commercially available starting materials. Dihydro-4-pyridone 3 possessed improved enzyme inhibition as measured by its k(inact) value against BioA, validating our pK(a)–based design strategy.